Students’ evaluation of using Google Classroom in project-based learning in faculty of English, Hanoi National University of Education (Journal of Contemporary Educational Policies and Practices, 2019)
Traditional classroom has so far been a common place for learning almost all school subjects and courses of different fields. In language teaching and learning within the 21st century context, the use of Google Classroom is not new, so is the research on the benefits and barriers of this virtual academic place. Being used as a supportive device for teaching and learning in several subjects over the past semesters, “Google Classroom” has become a familiar term among English majors in the Faculty of English, Hanoi National University of Education. This proposed study will explore the applications of this virtual academic environment in project-based learning, focusing on investigating students’ perspectives on its advantages and disadvantages, as well as their expectations and suggestions for an optimal use.
Keywords: 21st century; blended learning; Google Classroom; project-based learning